Epidemiology of pre-pregnancy body mass index (BMI) among mothers in Abu Dhabi, the United Arab Emirates - Taha, Zainab; Hassan, Ahmed Ali; Papandreou, Dimitrios (Frontiers in Global Women's Health, 2022)
Pre-pregnancy obesity is a risk factor for several health problems such as gestational diabetes, preeclampsia, labor induction, postpartum hemorrhage, and neonatal hypoglycemia. Being underweight is a risk factor for fetal growth restriction. Despite the negative impact of abnormal pre-pregnancy body mass index (BMI) (over and underweight) on pregnancy outcomes, a limited amount of studies has been conducted on the prevalence of pre-pregnancy over and underweight and associated factors in the United Arab Emirates (UAE). Thus, the aim of this study was to investigate the prevalence and factors associated with underweight, overweight, and obesity among mothers with children under the age of 2 years in Abu Dhabi, the UAE. A cross-sectional multicenter study was conducted in 2017 and included data from seven government health care centers in Abu Dhabi. Maternal pre-pregnancy BMI was calculated as the weight in kilograms (kg) divided by the square of the height in meters (m), (kg/m2). A total of 1,622 mother–child pairs were included in this study. Out of the 1,622 mothers, 43 (2.7%) were underweight, 1,068 (65.8%) were normal weight, 412 (25.4%) were overweight, and 99 (6.1%) were obese. Mothers with advanced maternal age (AMA) (≥35 years) were more likely to be overweight, odds ratio [OR] = 1.93, (95% confidence interval [CI] 1.52–2.3), p ≤ 0.001, and obese OR = 2.15 (95% CI 1.32–3.39), p = 0.001. Mothers with lower family income were more likely to be obese OR = 2.72 (95% CI 1.44–5.93), p = 0.002. Mothers with high parity (≥2) were more likely to be overweight OR = 1.91 (95% CI 1.49–2.50), p ≤ 0.001; obese OR = 1.76 (95% CI 1.06–2.92), p = 0.024; and less likely to be underweight OR = 0.52 (95% CI 0.27–0.94), p = 0.037. Obese mothers were more likely to deliver via cesarean section (CS) OR = 1.95 (95% CI 1.27–2.96), p = 0.002. This study provides valuable baseline information on the epidemiology of pre-pregnancy BMI in the UAE. The sociodemographic factors identified in the study can be used to target at-risk women. The study findings can also be used to develop contextualized strategies to prevent and manage complications associated with abnormal pre-pregnancy BMI in Emirati women.